PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MARK DYNAMICS INDONESIA MEDAN - Nababan, Tiorika; Sitorus, Syahrial; barus, Apriwati br (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
In the research conducted at PT. Mark Dynamics Indonesia Medan, the primary focus was to investigate the impact of organizational culture and job satisfaction on employee performance. The company, a foreign investment entity engaged in manufacturing ceramic gloves (hand former manufacturer), faced challenges related to the lack of organizational culture, particularly in terms of company values. The identified problem was reflected in employee turnover, indicating potential issues with job satisfaction. The research aimed to answer the formulated problem: "How is the effect of organizational culture and job satisfaction on employee performance at PT. Mark Dynamics Indonesia Medan?" The study employed several theories related to Human Resource Management, including Organizational Culture, Job Satisfaction, Performance, Organization, and Leadership. The research methodology used was a survey method with a descriptive quantitative approach, and the nature of the research was explanatory. Data collection involved interviews, questionnaires, and documentation studies. The data analysis method employed was multiple regression. The population of the research comprised all employees at PT. Mark Dynamics Indonesia Medan, totaling 95 employees. The study utilized a saturated sampling technique, involving all employees in the company as samples. The research findings supported the formulated hypotheses, indicating that both organizational culture and job satisfaction had positive and significant effects on employee performance. Additionally, job satisfaction emerged as the most dominant factor influencing employee performance. In summary, the study concluded that both organizational culture and job satisfaction, when considered simultaneously and partially, had a positive and significant impact on employee performance at PT. Mark Dynamics Indonesia. The insights from this research could be valuable for the company in addressing organizational culture issues and enhancing job satisfaction to improve overall employee performance and reduce turnover.